Chemical constituents and antimicroblal activity of two arieties of Etlingera Elatior flowers [electronic resource] /cNurul Iryani Muhamad Azhar - Nurul Iryani Muhamad Azhar, 1988- (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013